2006
DOI: 10.1007/s00726-006-0312-3
|View full text |Cite
|
Sign up to set email alerts
|

Chlorpromazine, clozapine and olanzapine inhibit anionic amino acid transport in cultured human fibroblasts

Abstract: We report here that chlorpromazine, a first generation antipsychotic drug, inhibits anionic amino acid transport mediated by system X(-) (AG) (EAAT transporters) in cultured human fibroblasts. With 30 microM chlorpromazine, transport inhibition is detectable after 3 h of treatment, maximal after 48 h (>60%), and referable to a decrease in V(max). Chlorpromazine effect is not dependent upon changes of membrane potential and is selective for system X(-) (AG) since transport systems A and y(+) are not affected. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Chronic administration of antipsychotic drugs to rats reduces frontocortical expression of EAAT4 (Segnitz et al 2009), consistent with the increased levels of EAAT4 in SZ found in this study. Antipsychotic drugs (chlorpromazine, clozapine and olanzapine) reduce EAAT protein levels in human fibroblasts (Marchesi et al 2006). Clozapine also enhances NMDA receptor function in rat brain by inhibiting the glycine transporter (Javitt et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic administration of antipsychotic drugs to rats reduces frontocortical expression of EAAT4 (Segnitz et al 2009), consistent with the increased levels of EAAT4 in SZ found in this study. Antipsychotic drugs (chlorpromazine, clozapine and olanzapine) reduce EAAT protein levels in human fibroblasts (Marchesi et al 2006). Clozapine also enhances NMDA receptor function in rat brain by inhibiting the glycine transporter (Javitt et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Clozapine’s therapeutic dose in clinical practice is generally assumed to lie between 0.1-1.7 μmol/L (de Leon et al 2020 ; Northwood et al 2023 ). Previous studies investigating clozapine’s effects on membrane transport of amino acids in human fibroblasts have shown decreased transport of aspartate when fibroblasts were exposed to a supratherapeutic dose of clozapine in the 50 μmol/L range (Marchesi et al 2006 ). In another study, 100 μmol/L clozapine, a dose 50 times higher than its therapeutic dose, significantly decreased tyrosine transport during a 1-min uptake period (Bongiovanni et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%